2011
DOI: 10.1055/s-0031-1275325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Decreasing Plasma Lipid Level from Imidazoline I-1 Receptor Activation in High Fat Diet-fed Mice

Abstract: The imidazoline I-1 receptor (I-1 R) agonists are widely used to lower blood pressure, but their effects on hyperlipidemia are still obscure. The present study is aimed to evaluate the possible mechanism(s) of I-1 R in the regulation of lipid homeostasis. Farnesoid X receptor (FXR) plays an important role in blood lipid homeostasis; however, the role of FXR in rilmenidine-induced blood lipid lowering action is still unknown. Thus, we administered rilmenidine, a selective agonist of I-1 R, into high fat diet-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…In the study, we found that an activation of imidazoline I-1 receptor by the specific agonist rilmenidine significantly improved high-fat diet-induced hepatic steatosis at the effective dose as described previously (Niu et al 2011). Also, this action of rilmenidine was reversed by pretreatment of the I-1 receptor antagonist, implying the role of I-1 receptor in the regulation of lipid homeostasis.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In the study, we found that an activation of imidazoline I-1 receptor by the specific agonist rilmenidine significantly improved high-fat diet-induced hepatic steatosis at the effective dose as described previously (Niu et al 2011). Also, this action of rilmenidine was reversed by pretreatment of the I-1 receptor antagonist, implying the role of I-1 receptor in the regulation of lipid homeostasis.…”
Section: Discussionsupporting
confidence: 84%
“…Although Hep G2 cells are hard to show the same as normal human hepatocytes totally, this cell line is introduced to offer an alternative and reliable model for studies on liver lipid metabolism (Wang et al 1988). Similar to the changes in primary culture of mouse hepatocytes (Niu et al 2011), oleic acid-induced lipid accumulation in Hep G2 cells that also improved by rilmenidine (Fig. 2).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations